2015
DOI: 10.1097/hjh.0000000000000402
|View full text |Cite
|
Sign up to set email alerts
|

Costs of cardiovascular disease prevention care and scenarios for cost saving

Abstract: This is the first study to report the costs of CVD prevention care in sub-Saharan Africa, based on prospectively collected operational data. The costs observed in our study are unaffordable in many countries in sub-Saharan Africa, highlighting the need for innovative financing mechanisms to fund CVD prevention care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
39
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(39 citation statements)
references
References 41 publications
0
39
0
Order By: Relevance
“…Our study demonstrated that implementation of CVD prevention care was feasible within a CBHI program. However, provision of high-quality care was resourceintense and involved considerable costs [12]. Rapid scaleup of CVD prevention care in SSA according to current WHO CVD prevention guidelines [2] may be too demanding, especially in settings where CBHI programs are not available.…”
Section: Insurance For Cardiovascular Disease Prevention In Nigeriamentioning
confidence: 99%
“…Our study demonstrated that implementation of CVD prevention care was feasible within a CBHI program. However, provision of high-quality care was resourceintense and involved considerable costs [12]. Rapid scaleup of CVD prevention care in SSA according to current WHO CVD prevention guidelines [2] may be too demanding, especially in settings where CBHI programs are not available.…”
Section: Insurance For Cardiovascular Disease Prevention In Nigeriamentioning
confidence: 99%
“…The authors of that study used a gross-costing method that was based on healthcare use and average per-unit cost data (17)(18)(19)(20)(21)(22). The cost of asthma-related hospitalizations, for example, was estimated by multiplying the number of asthma hospitalizations by the average cost for one hospitalization (7,23).…”
mentioning
confidence: 99%
“…Looking through bibliographic sources, we found out that researchers from many countries had attempted to model some healthcare processes for the recent years. In particular, some of them suggested forming interdisciplinary teams and practicing systems approaches to chronic disease treatment [1,2,10,11], analyzing the incidence of chronic non-infectious diseases and risks of their occurrence [12][13][14]; frontend medical assistance [15] and vertical equality [16], optimization of planning, designing and financing of health systems in accordance with the number of † For the source article, please refer to: Куликова О.М., Усачева Е.В., Шамис В.А., Нелидова А.В., Боуш Г.Д. Модель финансового обеспечения регионального здравоохранения.…”
Section: Introductionmentioning
confidence: 99%
“…These models accommodate for sociopolitical circumstances and determinants of the health system [2,[17][18][19][20][21]; healthcare finance through the public-private partnership mechanism [22], spatial and time development of the health system [23][24][25]. The above studies involved correlation and regression analysis [13,17,19], Poisson lognormal mixed model in the Bayesian framework fitted to the INLA efficient estimation procedure [23], cost effectiveness estimation method [14], decision tree, Markov chain, micromodels, discrete and dynamic event modeling [24,26], descriptive statistics, forecasting and simulation [19-21, 24, 25], market research [10].…”
Section: Introductionmentioning
confidence: 99%